2020
DOI: 10.21203/rs.3.rs-29340/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived barriers to the adoption of active surveillance in low-risk prostate cancer: A Qualitative Analysis of Community and Academic Urologists

Abstract: Background: Clinical practice guidelines recommend active surveillance as the preferred treatment option for low-risk prostate cancer, but only a minority of eligible men receive active surveillance, and practice variation is substantial. The aim of this study is to describe barriers to urologists’ recommendation of active surveillance in low-risk prostate cancer and explore variation of barriers by setting. Methods: We conducted semi-structured interviews among 22 practicing urologists, evenly distributed bet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…However, physicians’ predictions of a patient’s ability to adhere to a treatment protocol have been shown to be unreliable, whether made solely on subjective judgments of patient characteristics or based on patient behavior evidence in the medical record [ 64 , 65 ]. A potential solution is implementation of shared decision making, which may be underused in urology practice [ 66 , 67 ]. Rather than deciding subjectively who might have trouble adhering to an AS protocol, the urologist or care team could instead elicit values from the fully informed patient to arrive at treatment selection together.…”
Section: Discussionmentioning
confidence: 99%
“…However, physicians’ predictions of a patient’s ability to adhere to a treatment protocol have been shown to be unreliable, whether made solely on subjective judgments of patient characteristics or based on patient behavior evidence in the medical record [ 64 , 65 ]. A potential solution is implementation of shared decision making, which may be underused in urology practice [ 66 , 67 ]. Rather than deciding subjectively who might have trouble adhering to an AS protocol, the urologist or care team could instead elicit values from the fully informed patient to arrive at treatment selection together.…”
Section: Discussionmentioning
confidence: 99%
“…as biases of patient treatment preferences in favor of physician's own specialty treatment represented key barriers to choosing AS [10]. Ellis et al reported that urologists' major concerns in regard to offering AS to PC patients were risk of disease underestimation with limited technology, lack of a standard evidence-based protocol, perceived probability of patient's non-adherence, patients being anxious about biopsy side-effects, and several limitations resulting from various environmental factors [11]. Improving care and clinical outcomes in patients diagnosed with low-risk PC is an important challenge…”
mentioning
confidence: 99%